The Betic-Rifean endemism Antirrhinum australe, chorological novelty for the province of Seville - Medina-Gavilán, José Luis; González, Basilio (Botanica Complutensis, 2021)
The presence of Antirrhinum australe Rothm (Plantaginaceae) is confirmed in the province of Seville, being represented by two populations located on the edge of its distribution in the southwestern Iberian Peninsula. Within the phenotypic dimorphism that A. australe presents in the hairiness of its vegetative organs, all studied individuals are characterized by stems and leaves largely devoid of trichomes. Reproductive success is apparently high (fruit set > 80%), but the geographic and ecological marginality of these populations seem to be important risk factors for their conservation, without clear signs of demographic recruitment. We argue that these populations can be useful for the comparative study of morpho-functional traits of interest in the genus, from an ecological-evolutionary perspective.
Keywords: Antirrhinum australe; bald phenotype; conservation; southwestern Spain